Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/jce.13270
|View full text |Cite
|
Sign up to set email alerts
|

Substrate characterization and catheter ablation in patients with scar‐related ventricular tachycardia using ultra high‐density 3‐D mapping

Abstract: Ultra high-density mapping in patients with scar-related VT is feasible, safe and enables detailed insight into tachycardia mechanisms. Critical sites can be identified (1) by precise substrate characterization when VT is not inducible or hemodynamically not tolerated and (2) during short lasting episodes of VT in order to guide catheter ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…A 6‐French quadripolar diagnostic catheter (Inquiry, 5 mm spacing; St. Jude Medical) was positioned in the right ventricular apex. High‐density‐3D mapping was performed in all patients (Rhythmia, Boston Scientific, Marlborough, MA) as previously described using a 64‐electrode basket‐catheter (Orion, Boston Scientific) during sinus rhythm, ventricular pacing and/or VT as appropriate. The left ventricle was accessed via a femoral retrograde transaortic approach (9 French, Terumo, Leuven, Belgium) or by transseptal access using a fixed curve long sheath (SL0, 8 French, St. Jude Medical).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 6‐French quadripolar diagnostic catheter (Inquiry, 5 mm spacing; St. Jude Medical) was positioned in the right ventricular apex. High‐density‐3D mapping was performed in all patients (Rhythmia, Boston Scientific, Marlborough, MA) as previously described using a 64‐electrode basket‐catheter (Orion, Boston Scientific) during sinus rhythm, ventricular pacing and/or VT as appropriate. The left ventricle was accessed via a femoral retrograde transaortic approach (9 French, Terumo, Leuven, Belgium) or by transseptal access using a fixed curve long sheath (SL0, 8 French, St. Jude Medical).…”
Section: Methodsmentioning
confidence: 99%
“…The left ventricle was accessed via a femoral retrograde transaortic approach (9 French, Terumo, Leuven, Belgium) or by transseptal access using a fixed curve long sheath (SL0, 8 French, St. Jude Medical). A steerable long sheath (Agilis large curl, 8.5 French, St. Jude Medical) was used for transseptal mapping and ablation . To maintain deep sedation, patients received propofol (2 mg/mL, B. Braun, Melsungen, Germany) combined with boluses of fentanyl (0.1 mg/mL, Rotexmedica, Trittau, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Implementation of electroanatomical mapping systems to characterize LV scar geometry and “real‐time” catheter location is now used almost exclusively in VT ablative procedures has been a significant advance in this field. Mapping is now greatly assisted by the development of multielectrode catheters with smaller electrodes and spacing capable of rapid, ultrahigh density maps with elegant automatic annotation algorithms and improved spatial resolution . Integration of imaging modalities (eg, cardiac magnetic resonance imaging) is also being increasing used to guide ablation with improved outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…19 AIHW, Australian Institute of Health, Welfare and Aging heart failure have been shown to reduce mortality, 23 resolution. 30 Integration of imaging modalities (eg, cardiac magnetic resonance imaging) is also being increasing used to guide ablation with improved outcomes. 31 A major paradigm shift in the current era has been a transition from a conventional "standard" procedure where VT must be induced to a "substrate-based" approach, avoiding unnecessary procedural risk caused by hemodynamic compromise from inducing VT. A substrate-based approach uses techniques to locate key components of the VT circuit in sinus rhythm (without the need to induce VT).…”
Section: Possible Explanations For Temporal Trends In Vt Ablations mentioning
confidence: 99%
“…Multiple studies have identified distinct characteristics within ventricular scar and thereby proposed different targets and approaches for substrate‐based ablation. In the present study, Nührich et al . describe the application of a new “ultra‐high resolution” mapping system (Rhythmia HDx TM by Boston Scientific, Marlborough, MA, USA) to the characterization of scar for catheter ablation in the context of this evolution of the definition of the electroanatomic substrate for VT.…”
mentioning
confidence: 99%